2019
DOI: 10.31729/jnma.4240
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Thyroid Disorder in A Primary Care District Hospital of Nepal

Abstract: Introduction: Thyroid disorders are among the common endocrine disorders and may approximate diabetes in prevalence. District hospitals are in frontline to manage chronic disorders including thyroid. Primary care workforce of physicians and mid-level providers together deliver care in these hospitals. Few hospitals are equipped with tests to diagnose thyroid disorders. The objective of the study is to find the burden of thyroid disorder in a district hospital of Nepal.Methods: This was a descriptive cross sect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 9 publications
0
7
1
Order By: Relevance
“…Diabetes mellitus is associated with a higher prevalence of thyroid disease, and vice versa [ 24 ]. Studies in Nepal among thyroid comorbid DM were shown in category three after the depression and hypertension [ 25 ], although our study observed that 13% of thyroid patients had diabetes mellitus which was the first category before HIV and malaria.…”
Section: Discussioncontrasting
confidence: 65%
“…Diabetes mellitus is associated with a higher prevalence of thyroid disease, and vice versa [ 24 ]. Studies in Nepal among thyroid comorbid DM were shown in category three after the depression and hypertension [ 25 ], although our study observed that 13% of thyroid patients had diabetes mellitus which was the first category before HIV and malaria.…”
Section: Discussioncontrasting
confidence: 65%
“…Jayan et al, 11 Khatiwada et al 16 and Yadav et al 17 however have found a higher prevalence of 42% among female population in South Western Nepal and 40% in BPKIHS, Dharan and far Western Nepal respectively. In contrast, one of the study 18 in Far Western region of Nepal has revealed only 15% of thyroid dysfunction in females. In Indian population, an epidemiological study has reported higher prevalence of TD in females however lesser frequency than in Nepal accounting to 11.4%.…”
Section: Discussionmentioning
confidence: 82%
“…4 A study from eastern Nepal showed that out of a total of 599 patients , 13.68% were affected by hyperthyroidism whereas another cross sectional study done in a district hospital in Bayalpata ,Nepal showed thyroid disorders to be present in 17% of the study population with approximately one fourth having hyperthyroidism. 5,6 In a population survey done by Carlos et al involving almost 5000 non pregnant adults it was seen that subclinical hyperthyroidism was present in 5.33% where as true hyperthyroidism was seen in only 0.61%. 7 A population study in the US showed hyperthroidism to be be present in 1.3% (0.5% clinical and 0.7% subclinical).…”
Section: Introductionmentioning
confidence: 99%